Perilaku Pencarian Pengobatan Pada Penderita Kanker Payudara (Studi di Kabupaten Solok Provinsi Sumatera Barat) - Yulfira Media (Jurnal Pembangunan Nagari, 2022)
Cancer in West Sumatra is a problem that needs serious attention. The purpose of this article is to describe the treatment-seeking behavior in breast cancer patients and the factors behind the treatment-seeking behavior. The research method used is a combination of qualitative and quantitative descriptive methods. Data collection techniques were carried out through direct interviews with respondents, in-depth interviews with informants, and observation. The study's results revealed that the treatment-seeking behavior that breast cancer patients mostly carried out was medical treatment and traditional medicine (70%). Most of the respondents (77%) had already run some type of medical treatment (surgery, and chemotherapy). The reason some respondents did not take medical treatment was that their family did not allow it (43%), limited funds (29%), and fear (28%). The factors behind seeking treatment behavior are knowledge/perceptions and beliefs of the community, economic conditions and access to health services, and environmental and psychological factors. The recommendations proposed include optimizing socialization and education about breast cancer disease and control to the community, increasing community participation in early detection of breast cancer, increasing public awareness and participation in breast cancer screening and treatment by utilizing health workers in health facilities.